Fast Lossless Depth Image Compression - Wilson, Andy (Proceedings of the 2017 ACM International Conference on Interactive Surfaces and Spaces (ISS '17), 2017)
A lossless image compression technique for 16-bit single channel images typical of depth cameras such as Microsoft Kinect is presented. The proposed "RVL" algorithm achieves similar or better compression rates as existing lossless techniques, yet is much faster. Furthermore, the algorithm's implementation can be very simple; a prototype implementation of less than one hundred lines of C is provided. The algorithm's balance of speed and compression make it especially useful in interactive applications of multiple depth cameras on local area networks. RVL is compared to a variety of existing lossless techniques, and demonstrated in a network of eight Kinect v2 cameras.